I'm reading group action in textbook Algebra by Saunders MacLane and Garrett Birkhoff.

enter image description here enter image description here enter image description here

I have a problem of understanding the last sentence:

Since conjugation is an automorphism, any two conjugate elements have the same order.

Assume $x,y \in G$ are conjugate, then they are equivalent. As such, $gxg^{-1} = y$ for some $g \in G$. This means $gx = yg$. From here, I could not get how $x,y$ have the same order.

Could you please elaborate on this point?


Mac Lane and Birkhoff are saying that it's not obvious (at least not directly) that $x$ and $gxg^{-1}$ have the same order. But once we know that $x \mapsto gxg^{-1}$ is an automorphism then it becomes obvious, since all automorphisms preserve order.

To see why, let $\varphi : G \to G$ be an automorphism. Then let $x \in G$ have order $n$, and let $\varphi x$ have order $m$. Now

$$(\varphi x)^n = \varphi (x^n) = \varphi e = e$$ So $m$ divides $n$.


$$(\varphi^{-1} \varphi x)^m = \varphi^{-1}((\varphi x)^m) = \varphi^{-1} e = e$$ And $n$ divides $m$ too, so they must be equal.

There is also a direct computational proof for the conjugation isomorphism. It is basically the exact same proof as above, but writing $gxg^{-1}$ everywhere I wrote $\varphi$ above. I encourage you to try to prove it yourself!

I hope this helps ^_^

  • 5
    $\begingroup$ Thank you for actually explaining what the authors write and not just providing a different proof. $\endgroup$ – Carsten S Jul 2 '20 at 8:52

Since $y=gxg^{-1}$, we have

$$\begin{align} y^n&=\underbrace{(gxg^{-1})\dots(gxg^{-1})}_{n\text{ times}}\\ &=\underbrace{g\cdot x\cdot (g^{-1}g)\cdot\dots\cdot (g^{-1}g)\cdot x \cdot g^{-1}}_{n\text{ times }x}\\ &=gx^ng^{-1}, \end{align}$$

so, if $x^n=e$, then $y^n=e$, and vice versa (by the inverse of conjugation).


Suppose that $x, y \in G$ are conjugate. Hence $\exists g\in G$ such that: $gxg^{-1}=y$
Note that : $y^2=(gxg^{-1})gxg^{-1}=gx^2g^{-1}$ and also $x^2=g^{-1}y^2g$ . Now show using induction that $y^n=gx^ng^{-1}$ and also $x^n=g^{-1}y^ng$ for $n\in \mathbb N$
Let $|x|=m$ and $|y|=p$ and hence $y^m =gx^mg^{-1}=e$, which implies that $p$ divides $m$$ \tag{1}$.
But also, $x^p=g^{-1}y^pg=g^{-1}eg=e$, which implies that $m$ divides $p$. $\tag{2}$

By (1) and (2), $m=p$


If $gxg^{-1}=y$ and $x^n=e$, then $y^n=(gxg^{-1})^n=(gxg^{-1})(gxg^{-1})\cdots(gxg^{-1})=gx^ng^{-1}=e$.

Similarly, if $x=g^{-1}yg$ and $y^n=e$, then $x^n=g^{-1}y^ng=e.$

Thus, if $y$ and $x$ are conjugates, then $y^n=e\iff x^n=e$.

So if $r$ is the order of $y$ (the least positive $n$ such that $y^n=e$), it is the order of $x$ too.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.